EKSISTENSI MAJAS DALAM ALQUR'AN SEBAGAI KHAZANAH KEILMUAN ISLAM - Moh. Muhtador Nawafi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
Amin Alkhulli was mapping out the qur’anic studies into two big themes, dirasat ma hawl Alquran dan dirasat fi Alquran nafsih. From this classification could be seen that majaz as part of the second studies. Majaz was categorized by Alkhulli as part of the Qur’anic text grammatical structure. Making the qur’anic text as an object of the study, therefore the existence of majaz will give various discourses. The linguistic theory gave two perspectives on this, first stated that Alqur’an was not contended majaz, because majaz indicated to have the untruth content, whereas it was impossible for Alquran to give the improper information. Second, majaz was existed inside the qur’anic texts, because it was indicating the elegant and high expression of language. Here is the focus of this article, wherein besides of becoming part of the qur’anic text, majaz was also becoming Islamic studies discourses.